HUBUNGAN KADAR HEMOGLOBIN DAN FERITIN DENGAN GAMBARAN KONDUKSI SARAF PADA ANAK TALASEMIA BETA MAYOR - Windy Krisanti Kusuma Dewi,* Uni Gamayani,* Nushrotul Lailiyya,* Lelani Reniarti,** Nanan Sekarwana* (NEURONA, 2017)
INTRODUCTION BETA THALASSEMIA MAJOR IS INHERITED HEMOGLOBIN SYNTHESIS DISORDER FOUND IN THALASSEMIA BELT INCLUDING INDONESIA PERIPHERAL NEUROPATHY IS ONE OF ITS UNDERDIAGNOSED NEUROLOGICAL COMPLICATIONS RESULTS IN POOR MANAGEMENT OF THE PATIENTS